Clinic-wide Intervention Lowers Financial Risk and Improves Revenue to HIV Clinics Through Fewer Missed Primary Care Visits. (1st April 2015) - Gardner, Lytt I.; Marks, Gary; Wilson, Tracey E.; Giordano, Thomas P.; Sullivan, Meg; Raper, James L.; Rodriguez, Allan E.; Keruly, Jeanne; Malitz, Faye
Abstract : Abstract: We calculated the financial impact in 6 HIV clinics of a low-effort retention in care intervention involving brief motivational messages from providers, patient brochures, and posters. We used a linear regression model to calculate absolute changes in kept primary care visits from the preintervention year (2008–2009) to the intervention year (2009–2010). Revenue from patients' insurance was also assessed by clinic. Kept visits improved significantly in the intervention year versus the preintervention year ( P < 0.0001). We found a net-positive effect on clinic revenue of +$24, 000/year for an average-size clinic (7400 scheduled visits/year). We encourage HIV clinic administrators to consider implementing this low-effort intervention.